Implementation of Restorative Justice Policy Narcotics Crime in the Police in the East Kalimantan Police Area - Nurkotip Nurkotip; Slamet Riadi; Suasa Suasa (Khazanah Sosial, 2024)
This study aims to analyze the implementation of the Restorative Justice policy in the Handling of Narcotics Crimes in the Police in the East Kalimantan Regional Police. Qualitative descriptive research method. A total of 10 informants were determined purpossively, namely the Head of the National Narcotics Agency (BNN) of Balikpapan City, the Head of the Balikpapan Police Narcotics Investigation Unit and the Kutai Kartanegara Police, the Head of the Tanah Merah Samarinda BNN Rehabilitation Center, the Head of Medicine and Health of the East Kalimantan Police; Chairman of the Balikpapan City Legal Aid and Public Policy Studies Institute and addicts undergoing rehabilitation in Balikpapan City, plus observation and documentation. Data analysis includes collection, condensation, data presentation, and conclusion drawn. The results of the study show that the implementation of National Police Regulation Number 8 of 2021 concerning the Handling of Crimes Based on Restorative Justice in narcotics crimes in the East Kalimantan Police has not been effective. In terms of communication, it has shown success with effective policy transmission and clarity through various media and forums, but challenges in consistency of socialization and approach to vulnerable communities still need to be overcome. In terms of resources, there is a shortage of experts, limited rehabilitation facilities, and inadequate budget support. The disposition aspect shows a positive attitude from the implementers, although the involvement of local governments needs to be increased. The bureaucratic structure has been organized with clear SOPs, but the complexity of administrative procedures needs to be simplified to improve program accessibility. The study suggests that implementers increase the effectiveness of policies, such as additional training for law enforcement officials, and the opening of new rehabilitation facilities to reach vulnerable communities. The findings of the research have implications for policy makers, law enforcement, and the public, namely helping to overcome the narcotics problem in a more humane and effective way, in this case in the East Kalimantan Regional Police area.